Alterations in the E3 ligases Parkin and CHIP result in unique metabolic signaling defects and mitochondrial quality control issues. (July 2018) - Lizama, Britney N.; Palubinsky, Amy M.; McLaughlin, BethAnn
Abstract: E3 ligases are essential scaffold proteins, facilitating the transfer of ubiquitin from E2 enzymes to lysine residues of client proteins via isopeptide bonds. The specificity of substrate binding and the expression and localization of E3 ligases can, however, endow these proteins with unique features with variable effects on mitochondrial, metabolic and CNS function. By comparing and contrasting two E3 ligases, Parkin and C-terminus of HSC70-Interacting protein (CHIP) we seek to highlight the biophysical properties that may promote mitochondrial dysfunction, acute stress signaling and critical developmental periods to cease in response to mutations in these genes. Encoded by over 600 human genes, RING-finger proteins are the largest class of E3 ligases. Parkin contains three RING finger domains, with R1 and R2 separated by an in-between region (IBR) domain. Loss-of-function mutations in Parkin were identified in patients with early onset Parkinson's disease. CHIP is a member of the Ubox family of E3 ligases. It contains an N-terminal TPR domain and forms unique asymmetric homodimers. While CHIP can substitute for mutated Parkin and enhance survival, CHIP also has unique functions. The differences between these proteins are underscored by the observation that unlike Parkin-deficient animals, CHIP-null animals age prematurely and have significantly impaired motor function. These properties make these E3 ligases appealing targets for clinical intervention. In this work, we discuss how biophysical and metabolic properties of these E3 ligases have driven rapid progress in identifying roles for E3 ligases in development, proteostasis, mitochondrial biology, and cell health, as well as new data about how these proteins alter the CNS proteome. Highlights: Parkin is a RING E3 ligase mutated in forms of early-onset Parkinson's disease. Structure-function studies identify Parkin as a regulator of mitochondria. Parkin shares client proteins with Ubox E3 ligase CHIP. Recent studies reveal that CHIP is a key regulator of mitochondrial energetics. Uncovering the functions of such E3 ligases can advance therapy for CNS diseases.